education in values, an approach to strategies as a way for the collective construction of knowledge (Revista Electrónica REDINE, 2019)
The present research aims to establish the possible relationship between the degree of integration of Information and communication technologies and the level of ICT competencieswhich which have the teachers from University of Guayaquil, it is expressed in the level of use of platforms for the management of virtual educational content as a didactic resource for an efficient teaching-learning process. The data, which were obtained through a survey, were applied through statistics of the Academic Unit of the Faculty of Philosophy and Science. According to the results, it was found out, that the teaching staff of the University of Guayaquil has from low to intermediate level in all dimensions of ICT competence due to many personal and / or institutional factors, however, the majority of teachers that were participated in the study, positively perceives the main advantages of ICT in the teaching-learning process representing a strength to continue advancing in their training and professional advancement that will redound into practice the educational quality.